2018
DOI: 10.3390/bios8030070
|View full text |Cite
|
Sign up to set email alerts
|

3D Carbon Microelectrodes with Bio-Functionalized Graphene for Electrochemical Biosensing

Abstract: An enzyme-based electrochemical biosensor has been developed with 3D pyrolytic carbon microelectrodes that have been coated with bio-functionalized reduced graphene oxide (RGO). The 3D carbon working electrode was microfabricated using the pyrolysis of photoresist precursor structures, which were subsequently functionalized with graphene oxide and enzymes. Glucose detection was used to compare the sensor performance achieved with the 3D carbon microelectrodes (3DCMEs) to the 2D electrode configuration. The 3DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…Despite of the invincibleness graphene is an good conductor of heat, electricity and optically transparent [6,7]. Because of the amazing characteristics graphene has been selected for a broad range of applications ranging from electronics to optics bio-devices and sensors [8][9][10]. Recently Nano-technologists are quite enthusiastic about graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Despite of the invincibleness graphene is an good conductor of heat, electricity and optically transparent [6,7]. Because of the amazing characteristics graphene has been selected for a broad range of applications ranging from electronics to optics bio-devices and sensors [8][9][10]. Recently Nano-technologists are quite enthusiastic about graphene.…”
Section: Introductionmentioning
confidence: 99%
“…These types of biosensors can be used as an efficient indicator of sugar level for biological diagnoses. Hemanth et al [97] also reported an enzyme-focused electro-chemical biosensor. This biosensor was fabricated using a 3D pyrolytic carbon micro-electrode that was deposited with biologically functionalized rGO.…”
Section: Resultsmentioning
confidence: 99%
“…Hemanth et al [97] fabricated a bio-functionalized graphene 3D carbon electrode biosensor. The reduction and functionalization of Hummers-modified GO was obtained by treatment with branched polyethylenimine (PEI) in a single reaction [98].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, 3D-structured nanomaterials, e.g., graphene, have been used in electrochemical nano-biosensors, which could further enhance the sensitivity compared 2D-structures [ 19 ]. In another study, pyocyanin toxin from cystic fibrosis patients was detected with an amperometric electrochemical nano-biosensor.…”
Section: Pathogen Detection With Electrochemical Biosensorsmentioning
confidence: 99%